Influência da substituição de areia natural por pó de pedra no comportamento mecânico, microestrutural e eletroquímico de concretos - Almeida, Maria das Vitórias Vieira de (2006)
The construction industry is one of the largest consumers of natural raw materials, and concrete is considered today the most used material wide. This accentuated consumption of natural resources has generated concern with the preservation of the environment, and has motivated various studies related to the use of resid ues, which can partially or entirely substitute, with satisfactory performance, some materials such as the aggregate, and in so doing, decrease the impact on the environment caused by the produced residues. Research has been done to better understand and improve the microstructure of concrete, as well as to understand the mechanism of corrosion in reinforced steel. In this context, this work was developed aiming at discovering the influence of the substitution of natural sand by artificial sand, with rega rd to mechanical resistance, microstructure, and durability. To obtain the electrochemical parameters, an adaptation was made to the galvanostatic electrochemical method to study the corrosion in reinforced steel. Concretes of categories 20 MPa and 40 MPa were produced, containing natural sand, and concretes of the same categories were produced with artificial sand substituting the natural sand, and with the addition of sodium nitrate and sodium chloride. Due to the use of rock dust reject (artificial sand), an evaluation was made of its environmental risk. The results indicate that the concretes of category 20 MPa present a better performance than the concrete made with natural sand, thus making it a viable substitute. For the category 40 MPa, the better performance is from the concrete containing natural sand. The adaptation of the galvanostatic electrochemical technique to the study of the corrosion of reinforced steel within concrete proved to be valid for obtaining electrochemical parameters with a high degree of reliability, considering the number of degrees of freedom